1997
DOI: 10.1002/(sici)1097-0061(199708)13:10<973::aid-yea146>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes with Nutrient-controlled Expression by PCR-mapping in the YeastSaccharomyces cerevisiae

Abstract: We have used RNA fingerprinting by the mRNA Differential Display technique to identify new genes in the yeast Saccharomyces cerevisiae, expression of which is controlled by specific nutrient conditions. mRNA was isolated from cells grown on glucose medium into exponential and stationary phase, and from cells starved for nitrogen on glucose‐containing medium. To avoid interference with the large number of glucose‐repressible genes, a glucose‐repression‐deficient strain was used. Twenty different sets of arbitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…To study the response to glucose starvation, RNA was isolated 1 h after transferring cells of the four strains from SD to S medium. We analyzed two genes already characterized for this stress condition in yeast: HSP12 and SSA3 (Crauwels et al, 1997). Figure 4D shows that in the case of HSP12 all the strains showed high induction levels except LYCC 047, similar to what has been observed under other stress conditions.…”
Section: Stress Due To Glucose Starvationsupporting
confidence: 70%
“…To study the response to glucose starvation, RNA was isolated 1 h after transferring cells of the four strains from SD to S medium. We analyzed two genes already characterized for this stress condition in yeast: HSP12 and SSA3 (Crauwels et al, 1997). Figure 4D shows that in the case of HSP12 all the strains showed high induction levels except LYCC 047, similar to what has been observed under other stress conditions.…”
Section: Stress Due To Glucose Starvationsupporting
confidence: 70%
“…Most recently, it was shown that Sch9 phosphorylates Maf1 at seven distinct sites in vitro and that it thereby can not only partially inhibit nuclear accumulation of Maf1 after rapamycin treatment, but also completely block the repressive association between Maf1 and the RNA Pol III subunit Rpc82 (Huber et al 2009). In addition to ribosome biogenesis, Sch9 controls the expression of different tRNA synthetases, proteins involved in amino acid metabolism as well as translation initiation and elongation factors (Crauwels et al 1997b;Roosen et al 2005) and recent evidence suggests that Sch9 also controls the phosphorylation status of eIF2a (Urban et al 2007). Hence, Sch9 functions as a central coordinator of protein synthesis and this may explain why sch9D cells are characterized by a small cell size, since, indeed, the translational capacity of a cell is tightly coupled to the size threshold at which cells commit to cell division (Jorgensen et al 2002(Jorgensen et al , 2004.…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%
“…Several modifications of the original technique have been reported with some solutions to the key problems identified by some authors [17]. Stress responses have been studied using DDRT-PCR in C. elegans and S. cerevisiae [18-20]. DDRT-PCR has been applied in many laboratories to identify genes involved in signal cascades.…”
Section: Introductionmentioning
confidence: 99%